2014
DOI: 10.1242/jeb.088542
|View full text |Cite
|
Sign up to set email alerts
|

Variation in body condition during the post-moult foraging trip of southern elephant seals and its consequences on diving behaviour

Abstract: Mature female southern elephant seals (Mirounga leonina) come ashore only in October to breed and in January to moult, spending the rest of the year foraging at sea. Mature females may lose as much as 50% of their body mass, mostly in lipid stores, during the breeding season due to fasting and lactation. When departing to sea, post-breeding females are negatively buoyant, and the relative change in body condition (i.e. density) during the foraging trip has previously been assessed by monitoring the descent rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
69
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 45 publications
(73 citation statements)
references
References 49 publications
4
69
0
Order By: Relevance
“…increased bottom duration per dive cycle, shown in the electronic supplementary material, figure S8) suggests that seals gained a foraging benefit from achieving neutral buoyancy by being fat. A similar foraging benefit has also been suggested in a study [37] that assessed the relationship among stroking effort and dive duration in southern elephant seals, a species that undergoes similarly significant changes in their body density (buoyancy) during oceanic migrations [27].…”
Section: Discussion (A) Buoyancy Determines Locomotor Costs Of Swimmingsupporting
confidence: 63%
See 1 more Smart Citation
“…increased bottom duration per dive cycle, shown in the electronic supplementary material, figure S8) suggests that seals gained a foraging benefit from achieving neutral buoyancy by being fat. A similar foraging benefit has also been suggested in a study [37] that assessed the relationship among stroking effort and dive duration in southern elephant seals, a species that undergoes similarly significant changes in their body density (buoyancy) during oceanic migrations [27].…”
Section: Discussion (A) Buoyancy Determines Locomotor Costs Of Swimmingsupporting
confidence: 63%
“…However, recording at high sampling rates limits the recording period owing to limitations in logger memory or battery power [36]. Only one study, which used accelerometry, showed a change in stroking effort of southern elephant seals over their post-breeding foraging migrations (less than 80 days), but the study mainly focused on the validation of estimating seal density using stroking effort and swim speed [37]. The paucity of long-term acceleration data has hindered further understanding of the relationships among buoyancy, swimming costs and foraging behaviour in long distance migrants such as highly pelagic marine animals.…”
Section: Introductionmentioning
confidence: 99%
“…[19]. First, dives where SESs stopped actively swimming at the bottom (as indicated by a low vertical speed and null lateral acceleration, i .…”
Section: Methodsmentioning
confidence: 99%
“…Static acceleration is caused by the Earth's gravitational pull whereas dynamic acceleration results from the animal's movements (body waves, tail strokes, head motions). The static component corresponds to low frequencies and the dynamic one to higher frequencies (Génin et al, 2015;Richard et al, 2014).…”
Section: Dive Parametersmentioning
confidence: 99%
“…The lateral axis of the accelerometer contains information on putative turning and rolling movements (static acceleration) and on flipper stroke (dynamic acceleration) (Richard et al, 2014). Swimming effort was obtained by summing the absolute values of the local extrema of the lateral axis of the acceleration filtered with a band-pass filter which cuts frequencies bellow 0.44 Hz and above 1 Hz (Jouma'a et al, 2016;Richard et al, 2014).…”
Section: Mean Swimming Effort Indexmentioning
confidence: 99%